2009
DOI: 10.1038/ejhg.2008.250
|View full text |Cite
|
Sign up to set email alerts
|

Maternal transmission effects of the PAX genes among cleft case–parent trios from four populations

Abstract: Isolated cleft lip with or without cleft palate (CL/P) is among the most common human birth defects, with a prevalence of 1 in 700 live births. The paired box (PAX) genes have been suggested as candidate genes for CL/P based largely on mouse models; however, few human studies have focused on this gene family. This study tests for association between markers in four PAX genes and CL/P using a case-parent trio design considering parent-of-origin effects. Trios from four populations (76 from Maryland, 146 from Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 45 publications
3
43
0
2
Order By: Relevance
“…7E–F), it is possible that Pax7 may be involved in the development of human orofacial clefts or additional craniofacial disturbances. In agreement with this view, a recent study suggests a strong correlation of maternally transmitted single nucleotide polymorphisms of Pax7 and Pax3 with cleft lip with or without cleft palate (Sull et al 2009). Furthermore, from CS12–18, we have shown the expression of p75 NTR within the early migratory neural crest, cranial or dorsal root ganglia, sympathetic tissue, and gut wall (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…7E–F), it is possible that Pax7 may be involved in the development of human orofacial clefts or additional craniofacial disturbances. In agreement with this view, a recent study suggests a strong correlation of maternally transmitted single nucleotide polymorphisms of Pax7 and Pax3 with cleft lip with or without cleft palate (Sull et al 2009). Furthermore, from CS12–18, we have shown the expression of p75 NTR within the early migratory neural crest, cranial or dorsal root ganglia, sympathetic tissue, and gut wall (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…In this regard, it is interesting to note effects of maternal genotype and maternalspecific environmental modifiers such as smoking, drinking and vitamin intake during pregnancy on oral cleft susceptibility have been previously reported in various studies. 2,[10][11][12][13][14][15][16][17][18][19] However, it should be noted that the parental asymmetry tests we applied here do not specifically test for maternal effects which would be expected to occur via alterations of the in utero environment. Calculation of genomic inflation factors for the MAT and PAT tests showed a small increase for the MAT compared with the PAT in all categories, this increased inflation factor in the MAT does not discern the underlying cause, being consistent with either a true excess of biological associations with the maternally inherited alleles, or alternatively differing population structure between the two parental populations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous candidate gene studies have suggested evidence for PofO effects in CL/P providing a strong rationale for performing comprehensive analysis to identify unconventional modes of inheritance. [16][17][18][19] However, non-Mendelian inheritance patterns such as imprinting are generally ignored in conventional GWAS, as these tests ignore the differential effects of maternally and paternally inherited alleles on phenotype. Indeed, simple case-control GWAS are unable to address this question.…”
Section: Introductionmentioning
confidence: 99%
“…Considering cleft lip with or without cleft palate, the sex ratio is biased with more affected males than females and an excess of maternal transmission in sporadic cases has been reported for several disease-causing genes. [23][24][25][26] As cleft lip may harbor a social disadvantage and more males than females are affected, reduced fertility of affected individuals could lead to the observation of an excess of maternal transmission. Another example is hereditary cystatin C amyloid angiopathy (HCCAA), which is an autosomal dominant disease with high penetrance, responsible for brain hemorrhages in young normotensive adults.…”
Section: Discussionmentioning
confidence: 99%